Penatalaksanaan Fisioterapi Pada Kasus Post Pemasangan Open Reduction Internal Fixation Fraktur 1/3 Distal Humerus Sinistra Di RSUD Panembahan Senopati Bantul - Nugroho, Ahmad Rizal Bayu; , Agus Widodo, S.Fis, M.Fis (2015)
Background : 1/3 distal humeral fracture is a fracture that occurs in the middle third and suprakondiler, Events fracture can cause pain conditions, limitations ROM, edema, decreased muscle strength due to pain and functional impairment. Objective : To determine the benefits of Infrared, and Exercise to reduce pain , decrease edema , increase range of motion ( ROM ) , improve muscle strength , and improve functional ability. Results : From the results of therapy can be concluded that the decrease in VAS pain from T0 to T6 treatment can be seen, silent pain T0 ( value 3.4 ) and T6 ( value 0 ), whereas tenderness at T0 ( value 3.7 ) and T6 ( value of 0 ), and Pain Motion of T0 ( value 6.3 ) and T6 ( value 1.8 ). Edema measured by mideline of lateral epicondylus 6 cm proximal to T0 ( 26 cm ) and T6 ( value 24.5 cm ), lateral epicondylus 6 cm distal to T0 ( value 23.5 cm ) and T6 ( value 23.5 cm ), are to epicondylus 12 cm lateral to the proximal T0 (value 27 cm ), and T6 ( value 26 cm ) and 12 cm lateral to epicondylus distally from T0 to T6 ( value 21.7 cm ) LGS with Goneometer actively from T0 ( S = 00-150-750 ) and T6 ( S = 00-00- 1300 ), while for passive motion T0 ( S = 00-50-800 ) and T6 ( S = 00-00 -1400). Muscle strength in elbow Sinestra T0 ( values to 3- ) and T6 ( value 4 ). As for the functional ability of the index woodstock Rehab & Fitness at the elbow with the results obtained T0 therapy ( value 20.5 ) with a description of the worst pain / very heavy during the move, and at T6 ( value 7.5 ) with a description of a light but constant pain when to move. Conclusion : Infrared can reduce pain , edema , moderate exercise therapy can improve muscle strength , increase range of motion ( LGS ) , and improve functional activities .